Sugarcane Variety Census: Florida 1999 - B. Glaz; Robert A. Gilbert (EDIS, 2003)
This annual variety census of the Florida sugarcane industry for the 1999-2000 harvest season is the latest in a long series. Mill managers and independent growers supplied data for 99.7 percent of Florida's sugarcane acreage. (This estimate was based on information supplied by growers and mill managers, and factoring in that growers who previously supplied variety information for 1,198 acres did not submit information this year). As a result, the census contains much descriptive and useful information for the Florida sugarcane industry. This document is SS AGR 196, a publication of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2003. Reviewed March 2005.